Breast Cancer - From Biology to Medicine 2017
DOI: 10.5772/66902
|View full text |Cite
|
Sign up to set email alerts
|

ErbB2 Receptor in Breast Cancer: Implications in Cancer Cell Migration, Invasion and Resistance to Targeted Therapy

Abstract: Overexpression of ErbB2 is found in several types of human carcinomas. In breast tumors, ErbB2 overexpression is detected in up to 20% of patients. Breast cancers in with ampliication of ErbB2 are characterized by rapid tumor growth, lower survival rate and increased disease progression. The molecular mechanisms underlying the oncogenic action of ErbB2 involve a complex signaling network that tightly regulates malignant cell migration and invasion and hence metastatic potential. Recent eforts have been made to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…ERBB3 may participate in the development of different types of cancer by regulating the migration and invasion of tumor cells ( 12 , 13 ). A recent study has indicated that ERBB3 may promote the development of breast cancer by increasing the migratory and invasive abilities of breast cancer cells ( 9 ), while the increased degradation of ERBB3 mediated by NRDP1 was identified to reduce the migratory and invasive abilities of human glioma cells ( 10 ). In the present study, ERBB3 siRNA silencing was identified to significantly reduce the proliferative, migratory and invasive abilities of cervical cancer cells, indicating that ERBB3 expression is important for the migration and invasion of cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERBB3 may participate in the development of different types of cancer by regulating the migration and invasion of tumor cells ( 12 , 13 ). A recent study has indicated that ERBB3 may promote the development of breast cancer by increasing the migratory and invasive abilities of breast cancer cells ( 9 ), while the increased degradation of ERBB3 mediated by NRDP1 was identified to reduce the migratory and invasive abilities of human glioma cells ( 10 ). In the present study, ERBB3 siRNA silencing was identified to significantly reduce the proliferative, migratory and invasive abilities of cervical cancer cells, indicating that ERBB3 expression is important for the migration and invasion of cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the functionality of ERBB3 in the pathogenesis of this disease remains unclear. A previous study indicated that ERBB3 may promote the migration and invasion of breast cancer cells and increased resistance of cancer cells to targeted therapy ( 9 ). In contrast, degradation of ERBB3 mediated by E3 ubiquitin-protein ligase NRDP1 (NRDP1) was demonstrated to inhibit the migration and invasion of human glioma cells ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of individual gene function made easier by using computational analysis that aids in finding cellular interaction networks, and their associated cellular physiological mechanisms. The activation of ERBB2 associated downstream signaling pathways [7,9], will help in understanding the molecular mechanisms leading to breast cancer. Genomic location, function, catalytic activity, Protein structure and domains, interactive functional partner's, and post-translational modifications of the ERBB2 gene have been accumulated by Bioinformatics data analysis.…”
Section: Results:-mentioning
confidence: 99%
“…Moderate affinity and promiscuity of recognition still a proven challenge for targeting Protein-Protein Interactions (PPIs), despite the enormous research in the discovery of anticancer drugs using ERBB2/p130C. However, resistance to ERBB2-targeted treatments was reported due to the contribution of various factors [7,[9][10].…”
Section: Results:-mentioning
confidence: 99%
See 1 more Smart Citation